Sesamum indicum Leaf Extract as Environmentally Benign Inhibitor to Mitigate Mild Steel Corrosion in Cement Pore Solution - Gautam, Madhab; Bhattarai, Nootan Prasad; Bhattarai, Jagadish (Journal of Institute of Science and Technology, 2025)
Concrete is one of the most widely used building materials after water due to its exceptionally high compressive strength. However, mild steel-reinforced concrete (MSRC) structures often encounter the problem of premature corrosion of the reinforcement. This issue emphasizes the importance of developing effective strategies to mitigate corrosion using inhibitors and understanding corrosion-controlling mechanisms. This work evaluates the effectiveness of Sesamum indicum leaf extract (SILE) as an environmentally friendly corrosion inhibitor in a saturated lime water solution with a pH of approximately 12, which simulates a cement pore solution (CPS). For the aim, weight loss (WL) and polarization procedures were conducted over 4 months to assess the corrosion inhibitory ability of SILE at concentrations of 500, 1000, 2000, and 4000 ppm in CPS to mitigate embedded mild steel (EMS) corrosion at a laboratory temperature of 25°C. The maximum inhibition efficiency was observed at 4000 ppm SILE, achieving 93.9% and 81.7% inhibition rates as determined by WL and potentiodynamic polarization (PDP) techniques, respectively. Also, PDP studies revealed a decline in corrosion current density with increasing SILE concentrations, indicating its inhibitory action. By facilitating adsorption onto the EMS surface, secondary metabolites (SMs), like mostly the flavonoids, including polyphenols, alkaloids, and terpenoids in SILE, can impede cathodic, anodic, or both processes. White light interferometry (WLI) and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM/EDX) images supported the results of corrosion-inhibiting effectiveness of SILE to improve the corrosion-resistant properties of concrete by the development of passive layer on EMS.